Epidemiologic Features of Vulvovaginal Candidiasis in Women of Childbearing Age in a Combined Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Vulvovaginal Candidiasis is a reproductive tract infection which remains a common cause of morbidity adversely affecting women’s physical and emotional health. Vaginal discharge in the childbearing age group is the most common complaint encountered every day both by gynaecologists and general practitioners. Among the cases of symptomatic vaginal discharge, Bacterial vaginosis is the commonest cause followed by Candidiasis and Trichomoniasis. It is characterized by curd-like vaginal discharge and itching and is associated with considerable health and economic costs.Objective: To detect the prevalence of Candida species in patients with complaints of vaginal discharge of reproductive age group attending at Child Welfare Centre (CWC), Gynaecology Outpatient Department (GOPD) and Medical Inspection Room (MI Room) of Combined Military Hospital (CMH) Ghatail.Materials and Methods: A cross-sectional descriptive study was conducted at CMH Ghatail during the period of April 2017 to October 2017. A total of 183 patients of reproductive age group with the complaints of vaginal discharge attending CWC, GOPD and MI Room of CMH Ghatail were included in this study. Two specimens of High Vaginal Swabs (HVS) were collected from each patient, one for direct microscopy and another for culture. For every patient, two wet film preparations and two Gram’s staining were done. Specimens were cultured on Blood Agar Medium and Sabourad’s Dextrose Agar Medium. Identification of Candida species was carried out by Wet film, Gram’s staining and culture examination.Results: According to the results of this study, the prevalence of Vulvovaginal Candidiasis (VVC) was found in 57(31.15%) of the cases. The maximum number of patients 126(66.66%) were found between 26 years to 35 years of age group. On the other hand, amongst 57 VVC positive cases, 44(77.19%)were identified as Candida albicans and 13(22.81%) were Candida non-albicans.Conclusion: Candida albicans is the predominant organism amongst candida species identified from VVC in this study. The high prevalence necessitates adequate screening of woman with vaginal discharge in order to give appropriate treatment and to avoid complications associated with it.Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 13-16